Reduction of heat accumulated in a thermosyphon paddy bulk storage - Kiatsiriroat T. (2014)
The objective of this research work was to develop a thermosyphon paddy bulk storage for reducing heat accumulated due to paddy respiration. A prototype of thermosyphon paddy bulk storage and a mathematical model with lumped analysis for predicting the paddy bed temperature were conducted. The storage was a double-wall steel cylinder with 636 mm outside diameter and 1500 mm length. The evaporator section consisted of a set of 70 copper tubes with 3.0 m2 surface area. The condenser section is the upper body of the storage tank and was ventilated with controlled air. In this study, the paddy bed, the ambient air, and methanol were used as the heat source, heat sink and working fluid in the thermosyphon, respectively. The paddy bulk of 115 kg with 12.5% wet basis was placed in the evaporator section of the thermosyphon. From the experiment it was found that the paddy bed temperature could be reduced from 31-32 to 26-27°C within 15-20 hours. Moreover the actual overall heat transfer coefficient between the bed and the working fluid was evaluated to be about 4.3 W/m2 °C. The paddy bed temperature could be maintained at about 26-27°C for eight weeks and the paddy qualities, whiteness and head yield, were in very good condition. In addition, the mathematical model developed could be used to predict the paddy bed temperature accurately.